2017
DOI: 10.3390/molecules23010071
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide Nucleic Acid against MicroRNA miR-145-5p Enhances the Expression of the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) in Calu-3 Cells

Abstract: Peptide nucleic acids (PNAs) are very useful tools for gene regulation at different levels, but in particular in the last years their use for targeting microRNA (anti-miR PNAs) has provided impressive advancements. In this respect, microRNAs related to the repression of cystic fibrosis transmembrane conductance regulator (CFTR) gene, which is defective in cystic fibrosis, are of great importance in the development of new type of treatments. In this paper we propose the use of an anti-miR PNA for targeting miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 54 publications
4
76
0
Order By: Relevance
“…Despite the fact that comparison between the anti-miR-PNA and PNA-masking approaches has not been done in parallel in this study, by comparing our results to those published by Fabbri et al [35], the PNA masking approach appears to be more effective than the anti-miR-PNA approach on the increase of CFTR. The fold increases of CFTR protein were 2-to 2.5-fold and 6-to 8-fold when the anti-miR-PNA [33] and PNA masking (Figure 4) approaches were employed, respectively, when the PNAs were used at 2 µM. Moreover, very low effects using anti-miR-145 PNA were obtained at lower concentrations (unpublished data), while the miR145-maskingPNA was active even when used at 0.5 µM.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Despite the fact that comparison between the anti-miR-PNA and PNA-masking approaches has not been done in parallel in this study, by comparing our results to those published by Fabbri et al [35], the PNA masking approach appears to be more effective than the anti-miR-PNA approach on the increase of CFTR. The fold increases of CFTR protein were 2-to 2.5-fold and 6-to 8-fold when the anti-miR-PNA [33] and PNA masking (Figure 4) approaches were employed, respectively, when the PNAs were used at 2 µM. Moreover, very low effects using anti-miR-145 PNA were obtained at lower concentrations (unpublished data), while the miR145-maskingPNA was active even when used at 0.5 µM.…”
Section: Discussionmentioning
confidence: 96%
“…As far as the comparison between the miRNA inhibiting and the miRNA masking strategies, we would like to underline that we have elsewhere published data supporting the use of miR-145-5p targeting in CF, based on an antisense PNA to target miR-145-5p and enhance expression of the CFTR gene [33,34]. This conclusion was recently confirmed by Kabir et al, who demonstrated that miR-145 mediates TGF-β inhibition of synthesis and function of the CFTR in CF airway epithelia [35].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations